Real-Life Management of Patients with Retinal Vein Occlusion Using I-Macula Web Platform - Massimo Nicolò; Monica Bonetto; Raffaella Rosa; Donatella Musetti; Maria Musolino; Carlo Enrico Traverso; Mauro Giacomini (Journal of Ophthalmology)
Aim. Real-life evaluation in the management of patients affected by macular edema secondary to retinal vein occlusion. Material and Methods. A retrospective, observational study using the I-Macula Web platform. Results. Thirty-five patients (37 eyes; 15 females and 20 male) affected by RVO were analysed. At 12 months, there was a statistically significant improvement of best-corrected visual acuity (p=0.0235) and central macular thickness (p<0.0001). The mean change in visual acuity was 8.9 letters. Twenty-seven eyes underwent DEX implant (n=62; mean: 2.29) only. Of these, 8, 4, 14, and 1 eyes underwent 1, 2, 3, and 4 DEX implants, respectively. The remaining 10 eyes were also injected with ranibizumab (n=49; mean: 4.9). At 12 months, 12 eyes (32.5%) presented a dry macula, whereas the remaining 25 eyes (67.5%) still had macular edema. Mean interval between the first and second treatment (T1) and between the second and third treatment (T2) were 5.15 and (T2) 3.7 months, respectively. Where only DEX implants were received, T1 and T2 was 5.1 and 4.9 months, respectively. Conclusions. This study confirms that DEX implants and/or anti-VEGF drugs improve visual acuity and central macular thickness in patients affected by RVO.